1988
DOI: 10.1254/jjp.47.200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of etizolam (Depas) on production of superoxide anion by platelet-activating factor and N-formyl-methionyl-leucyl-phenylalanine-stimulated guinea pig polymorphonuclear leukocytes.

Abstract: Abstract-Effect of etizolam on platelet activating factor (PAF) and N-formyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…These results suggest that PAF had already released oxyradicals from the PMN leukocytes, and, hence, further release of oxyradicals by zymosan (for stimulation of leukocytes for luminometer study) was reduced. PAF activates PMN leukocytes to release oxyradicals (Aratani et al 1988;Smith et al 1984). A decreased release of oxyradicals by PMN leukocytes prestimulated with zymosan has been reported (Prasad et al 1990, 199I).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results suggest that PAF had already released oxyradicals from the PMN leukocytes, and, hence, further release of oxyradicals by zymosan (for stimulation of leukocytes for luminometer study) was reduced. PAF activates PMN leukocytes to release oxyradicals (Aratani et al 1988;Smith et al 1984). A decreased release of oxyradicals by PMN leukocytes prestimulated with zymosan has been reported (Prasad et al 1990, 199I).…”
Section: Discussionmentioning
confidence: 94%
“…The decrease in the myocardial contractility and function may therefore be due to PAFinduced release of oxyradicals from PMN leukocytes. Aratani et al (1988) have shown that PAF on incubation with guinea pig PMN leukocytes resulted in generation of 02-and this effect was maximal within five minutes. Smith et al (1984) have also reported that PAF in vitro stimulated human neutrophils to release O~-and found that maximum release occurred in sixty seconds.…”
Section: Discussionmentioning
confidence: 95%